(untitled) (In situ, 2024)
The paper presents the preliminary results of the archaeological excavations of the Burnum site conducted in 2022. As a logical sequence of previous research activities at the amphitheater and in its vicinity, archaeological research continued with the excavation of Probe 58, which had already been partly explored during 2020, with the purpose of collecting relevant data on the cultural layers created during the leveling of the terrain and preparatory works for the construction of the amphitheater and military training ground.